The Influence of Viral Marketing, Price Perceptions, and Product Quality on Consumer Purchasing Decisions at Richeese Factory - Putri, Naila Aisyah; Supriyono (International Journal of Economics (IJEC), 2024)
This research aims to analyze the effect of Viral Marketing, price perceptions, and product quality on consumer purchasing decisions at Richeese Factory. The population used in this study are consumers who are at least 17 years old and have made purchases at Richeese Factory Rungkut Madya. The sample used was 112 respondents with a nonprobability sampling method using purposive sampling technique. The data collection method in this study used a questionnaire or Likert scale by distributing questionnaires via google form, then analyzed with Partial Least Square (PLS). The results showed that Viral Marketing and product quality variables had a positive effect on purchasing decision variables. Meanwhile, the price perception variable does not have a positive effect on the purchasing decision variable.